Economic evaluation of micafungin versus caspofungin for the treatment of candidaemia and invasive candidiasis. Issue 6 (9th June 2013) - Neoh, C. F.; Liew, D.; Slavin, M. A; Marriott, D.; Chen, S. C.‐A.; Morrissey, O.; Stewart, K.; Kong, D. C. M.
Abstract Background Micafungin demonstrated non‐inferiority to caspofungin as definitive therapy for candidaemia and invasive candidiasis (IC) in a major randomised clinical trial. Aim The aim of this study was to investigate if micafungin is a cost‐saving option compared with caspofungin for treating candidaemia and IC. Methods A decision analytical model was constructed to capture downstream consequences of using either agent as initial therapy for candidaemia and IC. The main outcomes were treatment success and treatment failure (i.e. death, mycological persistence, emergent infection, clinical failure but microbiological success). Outcome probabilities and treatment pathways were derived from the literature. Cost inputs were from the latest Australian resources, and resource use was estimated by expert panel. The analysis was from the Australian hospital perspective. Sensitivity analyses using Monte Carlo simulation were conducted. Results Micafungin (AU52 816) was associated with a lower total cost than caspofungin (AU52 976), with a net cost‐saving of 160 per patient. This was primarily due to the lower cost associated with alternative antifungal treatment in the micafungin arm. Hospitalisation was the main cost‐driver for both arms. The model outcome was most sensitive to the proportion of treatment success in the micafungin arm. Uncertainty analysis demonstrated that micafungin had a 58% chance of being cost‐saving compared with caspofungin. Conclusions Micafungin was cost‐equivalent to caspofungin in treating candidaemia and IC, with variation in drug acquisition cost the critical factor.